PENGELOLAAN PEMBELAJARAN SAINS MELALUI KEGIATAN MENCAMPUR WARNA DALAM UPAYA MENINGKATKAN KRETIVITAS ANAK PADA KELOMPOK A DI RA DARUSSALAM KECAMATAN KAWALU KOTA TASIKMALAYA - Munawar Hadiatin; Tetin Nurfitri; Sri Ajeng Lestari (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
The problems faced in the learning process if observed are many factors that influence it, including the use of methods used by teachers in delivering learning that is not appropriate, the factor of lack of teachers providing opportunities for children to develop their creativity. The scientific method with a skill approach through color mixing is very appropriate to be given to early childhood, because science can stimulate children to be creative and active in exploring various ideas and ideas of children. The purpose of this study was: to determine the process of learning science in group A RA Darussalaam. To find out the increase in early childhood creativity in the A RA Darussalaam group after using the scientific method. This research is intended to improve and improve the learning process that has been carried out by the teacher and overcome problems that occur in the field. Therefore, this study uses classroom action research (CAR). The conclusions from this study are: The creativity ability of early childhood in the A RA Darussalam group is still not optimal, due to the lack of use of media or teaching aids in the learning process and the method used by the teacher only asks questions. answer and lecture only, this is an obstacle; The process of learning this color mixing skill is carried out from cycle I and cycle II. The results of the reflection in the first cycle of early childhood skills are still not optimal, because the teacher does not understand the method used. Therefore, it is continued with the next cycle with all improvements and the results of the child's skill abilities show an increase. Finally, in the second cycle, improvements were made, skills through color mixing could increase more maximally. The development of early childhood skills in Group A RA Darussalaam, Kawalu sub-district, Tasikmalaya City after taking action through the use of the science skills method showed an increase. The results of the children's grades in the first cycle who got grades developed according to expectations (BSH). And the results in cycle II showed a fairly high increase, which got a very well developed score (BSB).